Metabolic Reprogramming by Reduced Calorie Intake or Pharmacological Caloric Restriction Mimetics for Improved Cancer Immunotherapy - Eriau, Erwan; Paillet, Juliette; Kroemer, Guido; Pol, Jonathan G. (Cancers, 2021)
Caloric restriction and fasting have been known for a long time for their health- and life-span promoting effects, with coherent observations in multiple model organisms as well as epidemiological and clinical studies. This holds particularly true for cancer. The health-promoting effects of caloric restriction and fasting are mediated at least partly through their cellular effects—chiefly autophagy induction—rather than reduced calorie intake per se. Interestingly, caloric restriction has a differential impact on cancer and healthy cells, due to the atypical metabolic profile of malignant tumors. Caloric restriction mimetics are non-toxic compounds able to mimic the biochemical and physiological effects of caloric restriction including autophagy induction. Caloric restriction and its mimetics induce autophagy to improve the efficacy of some cancer treatments that induce immunogenic cell death (ICD), a type of cellular demise that eventually elicits adaptive antitumor immunity. Caloric restriction and its mimetics also enhance the therapeutic efficacy of chemo-immunotherapies combining ICD-inducing agents with immune checkpoint inhibitors targeting PD-1. Collectively, preclinical data encourage the application of caloric restriction and its mimetics as an adjuvant to immunotherapies. This recommendation is subject to confirmation in additional experimental settings and in clinical trials. In this work, we review the preclinical and clinical evidence in favor of such therapeutic interventions before listing ongoing clinical trials that will shed some light on this subject.